(untitled) (The Planet, 2024)
Introduction: Cholestatic jaundice in infancy especially neonatal cholestasis is the most common liver problem in infants and one of the most problematic challenges for pediatricians. Neonatal cholestasis has a number of causes, and accurate diagnosis is important in guiding appropriate therapy either surgical or medical. Aim of the study: This study aimed to identify the etiology and clinical profile of cholestatic jaundice in infancy. Methods and materials: This cross-sectional observational study was conducted at the Department of Pediatric Gastroenterology and Nutrition, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from January 2021 to January 2022. A total of 30 cases were selected purposively. Statistical analysis was done by using SPSS (Statistical Package for Social Science) version 20. Result: Biliary atresia (66.7%) was the commonest cause of cholestatic jaundice followed by idiopathic neonatal hepatitis (INH) (26.7%) & neonatal hepatitis (NH) (6.6). Jaundice, intermittent or persistent pale stool, and dark urine were found in all the cases, and hepatomegaly and splenomegaly were found in 95%, and 60% of cases respectively in biliary atresia (BA) and in 80% and 70% of cases respectively in NH and INH. Mean serum bilirubin was 11.7+3.6 mg/dl in infants with BA and 16.1+13.8mg/dl in those with NH and INH. Conclusion: This study concludes that biliary atresia is the most common cause of neonatal cholestasis. Most of the cases present late though jaundice appears by two weeks of life. So, early referral of these cases is important.